S97 Severity of lung but not liver disease impacts cardiovascular risk in alpha-1 antitrypsin deficiency. (12th November 2015) - Samanta, S; Saleh, AD; Gooptu, B; Marshall, A; Thorburn, D; Lomas, DA; Hurst, JR
Abstract : Introduction: Alpha-1 antitrypsin deficiency (AATD) is a genetic condition associated with COPD; patients homozygous for the mutant 'Z' allele (PiZZ) are predisposed to severe, early-onset emphysema of the lung, and also progressive fibrosis and cirrhosis of the liver. There is a well-known association between COPD and cardiovascular disease, with around 1 in 3 COPD deaths attributed to a cardiac cause. 1 We hypothesised that cardiovascular risk in AATD may be independently modified by the severity of lung and liver disease, through common or related pathophysiological processes. Methods: Cardiovascular risk was ascertained in 43 patients with PiZZ AATD using QRISK2 score and aortic pulse wave velocity (aPWV). These values were correlated with indicators of lung (FEV1, DLCO, KCO, RV) and structural liver disease (transient elastography and liver ultrasound). Results: The severity of airflow obstruction (FEV1), emphysema (gas transfer) and gas trapping (RV) all related to cardiovascular risk as assessed by aPWV and QRISK2, Table 1 . In contrast, there was no significant association between the presence or increased severity of structural liver disease, as assessed by ultrasound and transient elastography respectively, and either indicator of cardiovascular risk (p < 0.05). Conclusions: These findings demonstrate that the severities of emphysema and airflow obstruction are associated with increased cardiovascular risk in AATD. In contrast, there was no association between the severity of structural liver disease and cardiovascular risk. Therefore, in conclusion, cardiovascular risk varies in PiZZ A1AD patients according to disease phenotype. Reference: 1 McGarvey LP, et al . Thorax 2007;62 (5):411–15